Digital Transformation Strategy of Aerospace Industry - Pu Sun; Weijia Yuan; Fengli Sun; Qian Shi; Shengyou Shi; Guoqing Wang (中国工程科学)
Digital transformation will promote the development of new-quality productivity in manufacturing enterprises. The aerospace industry, as an important representative of high-end manufacturing, plays an irreplaceable role in the development of new-quality productivity. In the context of increasingly complex projects and rapid iteration of new technologies, the development model of the aerospace industry is facing significant challenges and urgently requires digital transformation to promote high-quality development of the industry. This study proposes the concept of digital transformation in the aerospace industry and identifies the challenges currently faced. It elaborates on the basic ideas of digital transformation in the aerospace industry and demonstrates the development goals for each stage toward 2040. Moreover, a development path for the digital transformation of the aerospace industry is proposed, including the construction of a research and innovation system for digital intelligence collaboration, a new model for intelligent production of aerospace products, a digital supply chain system based on industrial interconnection, new infrastructure and network security, and a basic guarantee system. Suggestions are further proposed to construct an integrated network within the aerospace industry, conduct research and application pilot on artificial intelligence big model technologies in the aerospace industry, establish a pilot zone for aerospace data circulation and trading, build a safe and controllable ecosystem for independent industrial software, and cultivate a digital talent team for the aerospace industry, thereby constructing a new development model and promoting the high-quality development of the aerospace industry.